HUBUNGAN PEMAKAIAN KB SUNTIK 3 BULAN DENGAN GANGGUAN MENSTRUASI PADA IBU DI WILAYAH KERJA UPTD PUSKESMAS SEKAR JAYA KABUPATEN OGAN KOMERING ULU - Apria Wilinda Sumantri (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
One of the most important problems faced by developing countries, such as in Indonesia, is the population explosion. The population explosion resulted in a rapid population growth rate due to the lack of knowledge and cultural patterns in the local community. To overcome these problems the Indonesian government has implemented a family planning program which began in 1968 by establishing the National Family Planning Agency which later became the National Family Planning Coordinating Board.The purpose of this study was to determine the relationship between the use of 3-month injectable birth control with menstrual disorders in mothers in the work area of the UPTD Puskesmas Sekar Jaya, Ogan Komering Ulu. The sampling technique uses the Accidental Sampling method with a sample size of 30 people. Research has been carried out on June 20 to July 19, 2019 found that there is a relationship between the relationship of the use of 3-month injection injections with menstrual disorders in women in the UPTD Puskesmas Sekar Jaya OKU District. With a p value of 0.017. It is hoped that this research can be information material for health workers and for health agencies, especially those in the KIA Sekar Jaya Health Center in an effort to increase family planning counseling and side effects from 3-month KB, namely: weight gain, changes in skin, headaches . For injectable family planning acceptors who experience menstrual cycle disorders to use non-hormonal contraceptives. Especially in the Work Area of UPTD Puskesmas Sekar Jaya.